Macroeconomic factors toward nonperforming loan in Bank Rakyat Tampin - Hassan, Nurul Ashikin (2011)
This project paper was attempted to examine the macroeconomic factors towards nonperforming loan in Bank Rakyat Tampin. The macroeconomic factors are Gross Domestic Product (GDP), inflation rate and unemployment rate. The objective of the study was wanted to determine whether there is relation between independent variables and dependent variable. Researcher also tries to find out which independent variable that gives more impact to dependent variable. Data that has been collected are from year 2005 to 2009 with yearly data. All data for the study was a secondary data. The method that will be use is EViews6. Frequency distributions will be used to obtained for all the personal data or classification variables. Regression will be used to describe the nature of the relationship between variables. Finally researcher will show how the changes in dependent variable cause the changes in independent variables by using regression.